Interchromosomal linkage disequilibrium and linked fitness cost loci associated with selection for herbicide resistance. Issue 3 (22nd February 2023) - Gupta, Sonal; Harkess, Alex; Soble, Anah; Van Etten, Megan; Leebens‐Mack, James; Baucom, Regina S.
Summary: The adaptation of weeds to herbicide is both a significant problem in agriculture and a model of rapid adaptation. However, significant gaps remain in our knowledge of resistance controlled by many loci and the evolutionary factors that influence the maintenance of resistance. Here, using herbicide‐resistant populations of the common morning glory ( Ipomoea purpurea ), we perform a multilevel analysis of the genome and transcriptome to uncover putative loci involved in nontarget‐site herbicide resistance (NTSR) and to examine evolutionary forces underlying the maintenance of resistance in natural populations. We found loci involved in herbicide detoxification and stress sensing to be under selection and confirmed that detoxification is responsible for glyphosate (RoundUp) resistance using a functional assay. We identified interchromosomal linkage disequilibrium (ILD) among loci under selection reflecting either historical processes or additive effects leading to the resistance phenotype. We further identified potential fitness cost loci that were strongly linked to resistance alleles, indicating the role of genetic hitchhiking in maintaining the cost. Overall, our work suggests that NTSR glyphosate resistance in I. purpurea is conferred by multiple genes which are potentially maintained through generations via ILD, and that the fitness cost associated with resistance in this species is likely a by‐product of genetic hitchhiking.